Odpowiedzi

2009-12-03T15:00:34+01:00

a) x = 2y
5x - 3y = 21

x=2y
(5*2y)-3y=21

x=2y
10y-3y=21

x=2y
7y=21

x=2y
y=3

x=2y
x=6

b) x = y + 1
2x - y = -2

x=y+1
2(y+1)-y=-2

x=y+1
2y+2-y=-2 |-2

y= -4

x=y+1
x=-4+1

x=-3

c) x + y = 6 |*(-2)
2x + y = 11

-2x-2y=-12
2x+y=11

-y=-1
y=1

x+y=6
x+1=6 |-1

x=5
1 5 1
2009-12-03T15:01:33+01:00
A.

x=2y
5*2y-3y=21
x=2y
10y-3y=21
x=2y
7y=21
x=2y
y=3
x=2*3
y=3
x=6
y=3

b.
x=y+1
2x-y=-2
x=y+1
2*(y+1)-y=-2
x=y+1
2y+2-y=-2
x=y+1
y=-4
x=-4+1
y=-4
x=-3
y=-4

c.
x+y=6
2x+y=11
x+y=6
2x-x=11-6
x+y=6
x=5
y=6-5
x=5
y=1
x=5

Pozdrawiam
2009-12-03T15:04:28+01:00
A) x = 2y
5x - 3y = 21
x=2y
5*2y-3y=21
x=2y
10y-3y=21
x=2y
3y=21/3
y=7
x=14


b) x = y + 1
2x - y = -2
x = y + 1
2*y + 1 - y = -2
x = y + 1
2y + 1- y = -2
y= -3
x = -2


c) x + y = 6
2x + y = 11
x=6-y
2*6-y + y = 11
x=6-y
12 -y + y = 11
x=6-y
-y + y = 11 - 12
y= -1
x=7